Sea urchin-shaped material as well as preparation method and application thereof

By using metal organic frame materials to synthesize the core-shell structure of spherical sea urchin-like material, the problems of low production and low selectivity of carbon materials in electrocatalytic hydrogen peroxide production are solved, and efficient and stable hydrogen peroxide production is achieved.

CN119615252AActive Publication Date: 2025-03-14TIANJIN UNIV

Patent Information

Application Number
CN202411784258.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing carbon materials have low production volume in electrocatalytic hydrogen peroxide production and tend to generate competitive product water through four electron pathways, reducing reaction selectivity.

Method used

By using metal organic frame materials as precursors, spherical sea urchin-like materials are synthesized by hydrothermal and two-stage calcination methods to form a core-shell structure rich in nanotubes, adjust the electron distribution state around the active site, and improve the selectivity and activity of hydrogen peroxide.

Benefits of technology

The hydrogen peroxide selectivity of more than 90% under a wide potential window, stability of more than 10 hours, and a hydrogen peroxide production effect of nearly 800 mg/L within 2 hours was achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615252A_ABST
    Figure CN119615252A_ABST
Patent Text Reader

Abstract

The invention discloses a sea urchin-shaped material which is integrally in a spherical sea urchin shape, and the diameter of the sea urchin-shaped material is 3.0-6.0 [mu] m; nanotubes are arranged on the periphery of the spherical sea urchin shape; small spheres with core-shell structures are uniformly embedded in the interior of the base body of the spherical sea urchin-shaped material and at the tops of part of the nanotubes. The invention further discloses a preparation method of the sea urchin-shaped material and application of the sea urchin-shaped material to preparation of a hydrogen peroxide electrode material through an electro-catalysis two-electron oxygen reduction reaction. The sea urchin-shaped material disclosed by the invention has excellent electro-catalysis two-electron oxygen reduction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysis, and in particular relates to a sea urchin-shaped material, a preparation method thereof, and use of an electrode material for preparing hydrogen peroxide through an electrocatalytic two-electron oxygen reduction reaction. Background Art

[0002] As a common oxidant, hydrogen peroxide is widely used in fields such as medical disinfection and wastewater treatment. In recent years, the oxygen reduction reaction based on the two-electron pathway is expected to replace the energy-intensive anthraquinone method and realize the clean production of hydrogen peroxide due to its sustainable advantage of in-situ production. Carbon materials, as typical electrocatalysts, have the advantages of rich surface active sites, fast electron transfer speed, and high stability. However, the production of hydrogen peroxide under the catalysis of pure carbon materials is relatively low, and most allotropes of carbon materials are more inclined to the four-electron pathway, generating competitive product water, reducing the reaction selectivity, and greatly limiting its application in electrocatalytic hydrogen peroxide production (see Chemical Engineering Journal 2024, 479.; Applied Catalysis B: Environmental 2022, 307. and Applied Catalysis B: Environmental 2024, 341.). Carbon materials are compounded with low-cost, abundant transition metals, combining the advantages of high conductivity of carbon materials and high activity and high selectivity of transition metal materials. The metal-support interaction is used to regulate the electron distribution state around the active sites, thereby regulating the binding strength between the active sites and the intermediate product *OOH, which can achieve high activity, high selectivity and high stability production of hydrogen peroxide.

[0003] At present, in order to achieve efficient production of hydrogen peroxide, different strategies for improving the catalytic performance of transition metal and carbon material composites have been reported, such as heteroatom doping, morphology regulation, etc. However, there are still few reports on the construction of electrocatalysts based on metal-coated core-shell structures to achieve hydrogen peroxide production. By carbonizing and phosphating two-dimensional nickel-based precursors, metal phosphide core-shell heterostructures can be anchored on carbon nanosheets to achieve efficient production of hydrogen peroxide (see Small Methods, 2024, 2301560.); structures with coated nickel metal particles can also be constructed based on three-dimensional porous carbon-derived melamine foam (see Journal of Materials Chemistry A, 2023, 11, 10204-10212.). In the construction process of core-shell structures, the choice of precursors is very important. Metal-organic framework materials can form a stable structure with uniform metal distribution and large carbon framework extension area through self-assembly of inorganic metal centers and ligands; by introducing additional compounds, it is expected to synthesize catalysts with specific structures. In this process, how to simplify the catalyst preparation process and reduce the types of raw materials input into the reaction is the key to efficient electrocatalytic production of hydrogen peroxide. The regulation of the core-shell structure morphology and shell thickness, as well as the synergistic effect between the external carbon layer and the internal metal also need to be further explored.

[0004] The present invention has been proposed to solve the above-mentioned problems. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a spherical sea urchin-like material and a preparation method thereof, and uses the spherical sea urchin-like material of the present invention in the field of electrode materials for electrocatalytic two-electron oxygen reduction reaction. The preparation method of the present invention uses MOF as a precursor, and synthesizes a sea urchin-like material rich in nanotubes by hydrothermal and two-stage calcination. The preparation method of the present invention uses a nanoflower-shaped nickel-based metal organic framework (Ni-MOF) as an intermediate, and obtains a spherical sea urchin-like structural material rich in nitrogen-doped carbon nanotubes by adding melamine and two-stage calcination; melamine is used as an additional carbon and nitrogen source, which decomposes into carbon fragments during calcination and generates a reducing gas NH3, which nitrogen-dopes the carbon structure; the calcined product retains the spherical structure of Ni-MOF as a whole, and during calcination, due to the reducing atmosphere of hydrogen, argon, ammonia, etc., Ni 2+It is reduced to Ni metal particles, and is wrapped in situ by a nitrogen-doped carbon layer to form a core-shell structure with Ni metal particles as the core and nitrogen-doped carbon layer as the shell, wherein the thickness of the shell nitrogen-doped carbon layer is 5-15nm and adjustable; Ni metal particles can catalyze the formation of carbon nanotube structure, extend to the periphery to form fine nitrogen-doped carbon nanotubes with a length of 40-150nm and a diameter of 10-20nm, distributed on the periphery of the spherical sea urchin-shaped material, and the nitrogen-doped carbon nanotubes are evenly distributed on the surface of the spherical sea urchin-shaped material; and according to TEM, it is found that small spheres with core-shell structure are evenly embedded at the top of some nanotubes and inside the spherical carbon matrix. The preparation method of the present invention can effectively regulate the morphology of the spherical sea urchin-shaped material, especially the shell thickness of the small spheres of the core-shell structure, by changing the amount of melamine. The obtained material is used as an electrode material for preparing hydrogen peroxide by electrocatalytic two-electron oxygen reduction reaction, which can promote the electron and mass transfer process, optimize the binding energy of the intermediate *OOH, and realize the efficient preparation of hydrogen peroxide.

[0006] The technical solution of the present invention is as follows:

[0007] The first aspect of the present invention discloses a sea urchin-like material, which is a spherical sea urchin-like material with a diameter of 3.0-6.0 μm; the outer periphery of the spherical sea urchin-like material is a nanotube; small spheres with a core-shell structure are uniformly embedded inside the matrix of the spherical sea urchin-like material and on the top of some nanotubes.

[0008] Preferably, the diameter of the core of the core-shell structure is 10-100 nm; the thickness of the shell layer of the core-shell structure is 5-15 nm.

[0009] Preferably, the nanotubes have a length of 40-150 nm and a diameter of 10-20 nm.

[0010] Preferably, the overall composition of the material is nitrogen-doped carbon; the core of the core-shell structure is Ni metal particles, and the shell of the core-shell structure is also nitrogen-doped carbon.

[0011] Preferably, the composition of the material is: Ni is (2-15) at%, C is (80-90) at%, and N is (1.5-6.0) at%. At% is atomic percentage.

[0012] The second aspect of the present invention discloses a method for preparing the sea urchin-shaped material, comprising the following steps:

[0013] (1) Preparation of Ni-MOF: a certain amount of N,N-dimethylformamide, anhydrous ethanol and deionized water are mixed uniformly to obtain solution A; a certain amount of terephthalic acid and nickel chloride hexahydrate are dissolved in solution A in sequence to obtain solution B; solution B is ultrasonicated for a period of time, reacted at 160° C. for 12 hours, separated and washed 3-4 times, and freeze-dried to obtain the Ni-MOF;

[0014] (2) preparing a mixture of Ni-MOF and melamine: dispersing the Ni-MOF and melamine obtained in step (1) in anhydrous ethanol in a certain proportion, mixing at a certain temperature for a period of time, and then heating and evaporating the ethanol to obtain a solid;

[0015] (3) Preparation of sea urchin-like material: The solid obtained in step (2) is heated to 525-550°C in a mixed atmosphere of hydrogen and argon for a first calcination for 2-3 hours; then the temperature is further raised to 1000-1200°C for a second calcination for 2-3 hours; thus, the sea urchin-like material is obtained.

[0016] Preferably, in step (2), the amount of Ni-MOF and melamine added is Ni-MOF: melamine in a mass ratio of 1: (1-3); first, stirring and mixing at 25° C. for 10-20 h, then heating to 60° C. and continuing stirring and mixing until the ethanol is evaporated to dryness.

[0017] Preferably, in the first stage of calcination in step (3), the volume ratio of hydrogen to argon is 1:9, the flow rate is set to 100-200 sccm, the temperature is 550°C, the heating rate is 2°C / min, and the holding time is 2h; the second stage of calcination temperature is 1100°C, the heating rate is 3°C / min, and the holding time is 3h.

[0018] The third aspect of the present invention discloses the use of the sea urchin-shaped material for preparing a hydrogen peroxide electrode material by electrocatalyzing a two-electron oxygen reduction reaction.

[0019] Beneficial effects of the present invention:

[0020] 1. The sea urchin-like material of the present invention comprises a small sphere with a core-shell structure, wherein the core is a Ni metal particle, and the shell is a nitrogen-doped carbon layer, and the thickness of the shell is adjustable from 5 to 15 nm. The small spheres with a core-shell structure are uniformly embedded in the carbon matrix and at the top of some nanotubes. Compared with the existing nitrogen-doped carbon materials with a core-shell structure, the small spheres with a core-shell structure of the present invention have a more stable structure. The sea urchin-like material of the present invention is used to prepare an electrode material for hydrogen peroxide with excellent two-electron oxygen reduction performance; the small spheres with a core-shell structure, the nitrogen-doped shell carbon and the internal core nickel metal particles give full play to the synergistic effect, so that *OOH has the best binding energy strength at the active site, achieving a hydrogen peroxide selectivity of more than 90% under a wide potential window, a stability of more than 10 hours, and a hydrogen peroxide production effect of nearly 800 mg / L within 2 hours. The material of the present invention combines the respective advantages of carbon materials and transition metal materials, giving full play to the high conductivity and stability of traditional carbon materials. After being compounded with transition metals, the electronic state around the active site is synergistically improved through metal-carrier interaction, so that the material has higher hydrogen peroxide selectivity and activity; and the formation of the core-shell structure can effectively prevent the escape of internal metal particles, and is a relatively stable structure.

[0021] 2. The preparation method of the sea urchin-like material of the present invention adopts a precursor of a metal organic framework material, which itself has a rich porous structure. Compared with the conventional zeolite imidazolate framework structure (ZIF) material, the sea urchin-like material of the present invention has a more stable structure. The preparation method of the present invention uses a hydrothermal and two-stage calcination method, which has simple steps, a short time, and relatively few types of reaction raw materials; after the raw materials are evenly mixed, the first stage of calcination allows melamine to be better converted into a g-C3N4 structure through polyaddition and thermal polymerization reactions, and a dispersed nanotube morphology is formed after the second stage of calcination. The material obtained by the preparation method of the present invention is used to prepare an electrode material for hydrogen peroxide, which better promotes electron and mass transfer, is conducive to the full diffusion of the reactant oxygen and the reaction product hydrogen peroxide, and provides a more suitable environment for the generation of the intermediate *OOH.

[0022] 3. The preparation method of the sea urchin-like material of the present invention provides an effective means for adjusting the shell thickness of the core-shell structure by adjusting the amount of melamine added. The preparation method of the present invention synthesizes a spherical sea urchin-like material with nanotubes of different densities on the periphery, and small spheres of the core-shell structure are uniformly embedded inside the matrix of the spherical sea urchin-like material and on the top of some nanotubes; thereby changing the electron density distribution inside and outside the small spheres of the core-shell structure, achieving precise control from the thickness of the carbon layer to the electrocatalytic performance, and clarifying the structure-activity relationship between morphology and performance. Melamine has multiple roles in the preparation of the material of the present invention: in terms of morphology, it serves as an additional carbon and nitrogen source to provide a source of growth for nanotubes, decomposes at high temperature to generate NH3 to reduce metal ions for nucleation, and achieves nitrogen doping of the outer carbon layer during calcination, further adjusting the electron distribution state around the active site. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of the Ni-MOF obtained in Example 1.

[0024] Figure 2 These are SEM images of Ni@C (a), Ni@NCNTs-1 (b), Ni@NCNTs-1.5 (c) and Ni@NCNTs-3 (d) obtained in Comparative Example 1 and Examples 1-3.

[0025] Figure 3 TEM images of Ni@C (a), Ni@NCNTs-1 (b), Ni@NCNTs-1.5 (c) and Ni@NCNTs-3 (d) obtained in Comparative Example 1 and Examples 1-3.

[0026] Figure 4 TEM images of Ni@C (a), Ni@NCNTs-1 (b), Ni@NCNTs-1.5 (c) and Ni@NCNTs-3 (d) with different carbon layer thicknesses obtained in Comparative Example 1 and Examples 1-3.

[0027] Figure 5 It is the XRD diagram of Ni@C, Ni@NCNTs-1, Ni@NCNTs-1.5 and Ni@NCNTs-3 obtained in Comparative Example 1 and Examples 1-3.

[0028] Figure 6 The performance diagram of the materials obtained in comparative example 1 and examples 1-3 for electrocatalytic two-electron oxygen reduction reaction is shown in the diagram, which corresponds to the rotating ring disk electrode polarization curve diagram (a) and selectivity diagram (b).

[0029] Figure 7 The stability diagram (a) and hydrogen peroxide production diagram (b) of the electrocatalytic two-electron oxygen reduction reaction obtained in Example 1 are shown. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described below in conjunction with specific implementation methods. It should be noted that the following examples are only used to illustrate and explain the present invention in detail, and the application scope of the present invention is not limited by the conditions in the examples.

[0031] Example 1

[0032] Step 1: Preparation of Ni-MOF: 32 mL of N,N-dimethylformamide, 2 mL of anhydrous ethanol and 2 mL of deionized water were mixed evenly to obtain solution A; 0.1246 g of terephthalic acid and 0.2229 g of nickel chloride hexahydrate were dissolved in solution A in sequence to obtain solution B; solution B was ultrasonicated for 30 min, transferred to a sealed autoclave and reacted at 160 ° C for 12 h, and then centrifuged in 70% ethanol aqueous solution (the speed was 10000 rpm for the first time and 6000 rpm for the rest) for separation and washing 3-4 times; freeze-dried to obtain Ni-MOF;

[0033] The SEM image of the obtained Ni-MOF is shown in Figure 1 As shown, it presents a spherical nanoflower morphology.

[0034] Step 2: Prepare a uniformly dispersed mixture of Ni-MOF and melamine: Take 0.2g of Ni-MOF prepared in step 1 and 0.3g of melamine and disperse them in 50mL of anhydrous ethanol, transfer to a heating mantle and stir at 25°C for 12h, then raise the temperature to 60°C and continue stirring until the ethanol is evaporated.

[0035] Step 3: Preparation of sea urchin-like material: The mixture obtained in step 2 is placed in a quartz boat, and then placed in a quartz tube of a tube furnace; in a mixed atmosphere of hydrogen and argon with a volume fraction of 1:9, the temperature is increased to 550°C at a heating rate of 2°C / min and maintained for 2 hours to fully generate a graphitized carbon nitride structure; the temperature is continued to be increased to 1100°C at a heating rate of 3°C / min and maintained for 3 hours to form a nitrogen-doped nanotube structure; the obtained material is named Ni@NCNTs-1.5.

[0036] The SEM image of Ni@NCNTs-1.5 obtained by the test is as follows Figure 2 As shown in c, the obtained material is spherical sea urchin-shaped; TEM image is shown in Figure 3 As shown in Figures 4c and 4d, it can be seen that the spherical sea urchin-shaped outer periphery is nanotubes, that is, nitrogen-doped carbon nanotubes are evenly distributed on the periphery of the sea urchin-shaped material, the length of the nanotubes is about 80nm, and the diameter is about 15nm; small spheres with a core-shell structure are evenly inlaid on the top of some nanotubes, the shell thickness of the small spheres with a core-shell structure is about 8.96nm, and the diameter of the core is about 58nm.

[0037] Comparative Example 1: Same as Example 1, but without adding melamine.

[0038] The steps are the same as in Example 1.

[0039] Step 2: Same as step 3 of Example 1; the obtained material is named Ni@C. The SEM image of Ni@C obtained by testing is as follows Figure 2 a; Figure 2As can be seen from a, compared with the precursor Ni-MOF, the surface of Ni@C is rougher and loaded with metal particles, but no nanotube distribution is observed; the TEM image of Ni@C is shown in Figure 3 a, as shown in 4a; Figure 3 a and 4a, the diameter of the metal particles is relatively large, about 120 nm; the core-shell structure is not obvious, and the thickness of the carbon layer is 2.86 nm.

[0040] Example 2

[0041] The steps are the same as in Example 1.

[0042] Step 2: Prepare a uniformly dispersed mixture of Ni-MOF and melamine: Disperse 0.2 g of Ni-MOF prepared in step 1 and 0.2 g of melamine in 50 mL of anhydrous ethanol, transfer to a heating mantle and stir at 25 ° C for 12 h, then heat to 60 ° C and continue stirring until the ethanol evaporates;

[0043] Step 3 is the same as in Example 1; the obtained material is named Ni@NCNTs-1. The SEM image of Ni@NCNTs-1 obtained by testing is as follows Figure 2 As shown in b, it can be seen that the obtained material is spherical sea urchin-shaped; TEM image is shown in Figure 3 As shown in Fig. 4b, it can be seen that there are relatively sparse nanotubes distributed on the surface; small spheres with core-shell structure are also evenly embedded on the top of some nanotubes. The shell thickness of the small spheres with core-shell structure is about 5.75nm, and the diameter of the core is about 46nm.

[0044] Example 3

[0045] The steps are the same as in Example 1.

[0046] Step 2: Prepare a uniformly dispersed mixture of Ni-MOF and melamine: Disperse 0.2 g of Ni-MOF prepared in step 1 and 0.6 g of melamine in 50 mL of anhydrous ethanol, transfer to a heating mantle and stir at 25 °C for 12 h, then heat to 60 °C and continue stirring until the ethanol evaporates;

[0047] Step 3 is the same as in Example 1; the prepared catalyst is named Ni@NCNTs-3; the SEM image of Ni@NCNTs-3 obtained by testing is as follows Figure 2 As shown in d, it can be seen that the obtained material is spherical sea urchin-shaped; TEM image is shown in Figure 3 As shown in Figures 4d and 4d, it can be seen that there are relatively sparse nanotubes distributed on the surface; small spheres with core-shell structure are evenly embedded on the top of some nanotubes. The shell thickness of the small spheres with core-shell structure is about 11.70nm, and the diameter of the core is about 58nm.

[0048] Figure 5The XRD patterns of Ni@C, Ni@NCNTs-1, Ni@NCNTs-1.5 and Ni@NCNTs-3 obtained in Comparative Example 1 and Examples 1-3 are shown in Table 1. Figure 5 It can be seen that the material composition is graphite carbon and Ni. Table 1 shows the element contents of the materials prepared in Examples 1-3 and Comparative Example 1, measured by SEM-EDS.

[0049] Table 1 Element content

[0050]

[0051] Example 4: Ni@C, Ni@NCNTs-1, Ni@NCNTs-1.5 and Ni@NCNTs-3 obtained in the comparative example and the example are used for electrocatalytic two-electron oxygen reduction reaction.

[0052] The method is as follows: the activity, selectivity and stability of the two-electron oxygen reduction reaction are tested on a rotating ring disk disk electrode, and the electrolyte is 0.1M KOH; wherein the Ag / AgCl electrode is used as a reference electrode and the platinum mesh is used as a counter electrode; 5 mg of the materials obtained in comparative example 1 and examples 1-3 are respectively dispersed in 690 μL of water, 300 μL of ethanol and 10 μL of 5 wt% Nafion solution, and ultrasonically treated for 1 h; 5 μL is drop-casted on the glassy carbon of the rotating ring disk disk electrode as a working electrode, and the mass loading is 0.1 mg / cm 2 ; The voltage is corrected by the following formula: E RHE =E Ag / AgCl +0.059V×pH+0.197V.

[0053] Before the measurement, cyclic voltammetry (CV) was performed at a scan rate of 50 mV / s for 10 cycles in a nitrogen atmosphere to achieve a stable electrochemical environment. Oxygen was introduced and the polarization curve was measured by linear sweep voltammetry (LSV), where the ring voltage was 1.4 V, the disk voltage was 0-1 V, and the scan rate was 5 mV / s. The H2O2 selectivity and the number of transferred electrons were calculated by the formula: and Calculate; where N C is the platinum ring collection efficiency, I d is the disk current, I r is the ring current.

[0054] The H2O2 production test was carried out in an H-type electrolytic cell, and the electrolyte was 0.1M KOH; the materials obtained in Comparative Example 1 and Examples 1-3 were drop-coated on carbon paper as working electrodes, and the loading amount was 0.1 mg / cm 2 , Ag / AgCl electrode as reference electrode, graphite rod as counter electrode; Ce ion titration and UV-visible spectrophotometry were used to determine H2O2 and calculate its concentration; Reaction basis: 2Ce4+ +H2O2→2Ce 3+ 2H + O2; the Faraday efficiency calculation formula is: Among them, C H2O2 is the cumulative concentration of H2O2 in the H pool, V cell is the volume of cathode electrolyte, F is the Faraday constant, I is the current, and t is the test time.

[0055] Figure 6 The materials obtained from the comparative examples and the examples are used for electrocatalytic two-electron oxygen reduction reaction performance diagrams, corresponding to the rotating ring disk electrode polarization curve diagram (a) and selectivity diagram (b). Figure 7 The graphs (a) and (b) are the stability graph of the electrocatalytic two-electron oxygen reduction reaction and the hydrogen peroxide production graph of the material obtained in Example 1. Figure 6 and Figure 7 It can be seen that the Ni@NCNTs-1.5 material obtained in Example 1 has the best performance for electrocatalytic two-electron oxygen reduction reaction; it has a hydrogen peroxide selectivity of more than 90% in a wide potential window, a stability of more than 10 hours, and a hydrogen peroxide production effect of nearly 800 mg / L within 2 hours.

[0056] Comparative Example 2

[0057] The technical solution reported in Small Methods, 2024, 2301560. is used. First, a two-dimensional nanosheet precursor is synthesized by a hydrothermal method, and then the metal phosphide core-shell heterostructure is anchored on the nanosheet after two high-temperature calcinations (one carbonization and one phosphating), and the thickness of the nickel phosphide shell is about 8nm. This method uses a preparation process of hydrothermal + calcination + phosphating, the process is cumbersome, the shell thickness of the core-shell structure is difficult to control, and the output of electrocatalytic production of hydrogen peroxide is less than 1 / 3 of the present invention.

[0058] Comparative Example 3

[0059] The technical solution reported in Journal of Materials Chemistry A, 2023, 11, 10204-10212 was used. Commercially available melamine sponge was used as a precursor and synthesized with graphene oxide, urea, boric acid, and nickel salt by a hydrothermal-calcination method. This method has a large variety of raw materials and does not further regulate the core-shell structure. The prepared catalyst has a two-electron oxygen reduction selectivity of less than 90%.

[0060] The above description is only used to introduce the specific implementation methods of the present invention in detail, but the technical solution proposed by the present invention is not limited to the above method. Without departing from the basic principles of the present technology, equivalent modifications and changes made by those skilled in the art to the technology proposed by the present invention should be included in the scope of the claims of the present invention.

Claims

1. A sea urchin-shaped material, characterized in that: The material is in the shape of a spherical sea urchin with a diameter of 3.0-6.0 μm. The outer periphery of the spherical sea urchin is a nanotube. Small spheres with a core-shell structure are evenly embedded inside the matrix of the spherical sea urchin material and on the top of some nanotubes.

2. The sea urchin-shaped material according to claim 1, characterized in that: The diameter of the core of the core-shell structure is 10-100 nm; the thickness of the shell layer of the core-shell structure is 5-15 nm.

3. The sea urchin-shaped material according to claim 1, characterized in that: The nanotubes are 40-150nm in length and 10-20nm in diameter.

4. The sea urchin-shaped material according to claim 1, characterized in that: The overall composition of the material is nitrogen-doped carbon, and the core of the core-shell structure is Ni metal particles.

5. The sea urchin-shaped material according to claim 4, characterized in that: The composition of the material is: Ni is (2-15) at%, C is (80-90) at%, and N is (1.5-6.0) at%.

6. The method for preparing the sea urchin-shaped material according to any one of claims 1 to 5, characterized in that: The steps include: (1) Preparation of Ni-MOF: a certain amount of N,N-dimethylformamide, anhydrous ethanol and deionized water are mixed uniformly to obtain solution A; a certain amount of terephthalic acid and nickel chloride hexahydrate are dissolved in solution A in sequence to obtain solution B; solution B is ultrasonicated for a period of time, reacted at 160° C. for 12 hours, separated and washed 3-4 times, and freeze-dried to obtain the Ni-MOF; (2) preparing a mixture of Ni-MOF and melamine: dispersing the Ni-MOF and melamine obtained in step (1) in anhydrous ethanol in a certain proportion, mixing at a certain temperature for a period of time, and then heating and evaporating the ethanol to obtain a solid; (3) Preparation of sea urchin-like material: The solid obtained in step (2) is heated to 525-550°C in a mixed atmosphere of hydrogen and argon for a first calcination for 2-3 hours; then the temperature is further raised to 1000-1200°C for a second calcination for 2-3 hours; thus, the sea urchin-like material is obtained.

7. The preparation method according to claim 6, characterized in that: In step (2), the amount of Ni-MOF and melamine added is a mass ratio of Ni-MOF to melamine of 1:(1-3); first, the mixture is stirred and mixed at 25° C. for 10-20 h, then the temperature is raised to 60° C. and the stirring and mixing is continued until the ethanol is evaporated to dryness.

8. The preparation method according to claim 6, characterized in that: In step (3), the first stage of calcination has a volume ratio of hydrogen to argon of 1:9, a flow rate of 100-200 sccm, a temperature of 550°C, a heating rate of 2°C / min, and a holding time of 2h; the second stage of calcination has a temperature of 1100°C, a heating rate of 3°C / min, and a holding time of 3h.

9. Use of the sea urchin-shaped material according to any one of claims 1 to 5 for preparing a hydrogen peroxide electrode material by electrocatalytic two-electron oxygen reduction reaction.

Citation Information

Patent Citations

  • Urchin-like magnetic nanoparticles as well as preparation and application thereof

    CN105688794A

  • MOF-derived Ni monatomic loaded nitrogen-doped carbon hydrogen storage catalyst as well as preparation method and application thereof

    CN116212915A

  • Carbon nanotube coated metal particle oxygen reduction electrocatalyst, preparation method thereof and application of carbon nanotube coated metal particle oxygen reduction electrocatalyst in fuel cell

    CN116247226A

  • Lightweight core-shell structure urchin-like NiO / Ni-coated CNTs composite wave-absorbing material and preparation method thereof

    CN116871528A

Cited By

  • Catalyst material integrated with Au-Ir cascade catalytic sites as well as preparation method and application of catalyst material

    CN121041454A